Growth and Production Response of Mung Beans (Vigna radiata L.) Against Giving Gamal Leaf LOF - Wulandari, Fany Inayah; Rr. Liliek Dwi Soelaksini; Jumiatun; Rudi Wardana (International Integrated Agricultural Journal (IIAJ), 2025)
The importance of good nutritional intake has led to a high demand for mung beans. One of the efforts to increase mung bean production through the application of Gamal Leaf Liquid Organic Fertilizer. This study aims to examine the growth response and production of mung beans through the application of Gamal Leaf Liquid Organic Fertilizer. This research was carried out on agricultural land in Antirogo Village, Jember Regency from June to September 2024. This study consists of 6 levels of treatment, namely: Without Gamal Leaf Liquid Organic Fertilizer, Gamal Leaf Liquid Organic Fertilizer 40 ml/l, Gamal Leaf Liquid Organic Fertilizer 60 ml/l, Gamal Leaf Liquid Organic Fertilizer 80 ml/l, Gamal Leaf Liquid Organic Fertilizer 100 ml/l, Gamal Leaf Liquid Organic Fertilizer 120 ml/l. The results of this study showed that the application of Gamal Leaf Liquid Organic Fertilizer 120 ml/l had a real effect on the number of sampled pods (52.25 seeds), the weight of wet pods per sample (44.95 grams) and had a very real effect on the weight of perplot dry seeds (608.5 grams), the weight of sampled dried seeds (41.40 grams).